2015
DOI: 10.1002/er.3292
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of zinc-loaded hollow glass microspheres (HGMs) for hydrogen storage

Abstract: The greatest challenge for a feasible hydrogen economy lies on the production of pure hydrogen and the materials for its storage with controlled release at ambient conditions. Hydrogen with its great abundance, high energy density and clean exhaust is a promising candidate to meet the current global challenges of fossil fuel depletion and green house gases emissions. Extensive research on hollow glass microspheres (HGMs) for hydrogen storage is being carried out world-wide, but the right material for hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[13][14][15][16] Hollow glass microspheres (HGM) are widely used in various fields. [17][18][19] HGM-TiO 2 is an important composite material and became commercially available. It is easy to separate and recover.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Hollow glass microspheres (HGM) are widely used in various fields. [17][18][19] HGM-TiO 2 is an important composite material and became commercially available. It is easy to separate and recover.…”
Section: Introductionmentioning
confidence: 99%
“…The intriguing aspect of low thermal conductivity inherent in HGMs, a characteristic that contributes to their limited hydrogen release capacity, has sparked considerable interest among researchers. , A strategic approach to circumvent this limitation involves doping HGMs with transition metals or metal dopants. Elements such as magnesium and iron, cobalt, , and zinc have been employed to enhance the heat transfer characteristics of the microspheres, consequently amplifying their hydrogen storage capabilities.…”
Section: Improving Hydrogen Storage Performance Of Glass Microspheresmentioning
confidence: 99%
“…However, excessive Zn concentrations led to pore closure and surface deposition, akin to iron and cobalt effects. An optimal 2.0 wt % Zn concentration achieved the highest hydrogen adsorption of 3.26 wt % at 200 °C and 10 bar, demonstrating that high Zn levels can aggregate, closing pores and forming surface patches, thus narrowing gap widths. , Additionally, Moosavi et al have contributed insights revealing that the porosity of alkali borosilicate glass hollow glass beads is significantly influenced by the acid leaching duration during their preparation. It was found that extending the leaching time from 30 min to 1 h led to an expansion in the pore size range from 0 to 100 to 1000 nm.…”
Section: Improving Hydrogen Storage Performance Of Glass Microspheresmentioning
confidence: 99%
“…A thermally driven release requires temperatures of 200-400°C (473.15-673.15 K), depending on required hydrogen flow rate, sphere material and sphere dimension, and is also limited by the thermal conductivity of the spheres [26]. Another option is to utilize an infrared lamp, which has been under research since 1998 mainly but not only by the group of Shelby [20,22,24,25,27,28].…”
Section: Hollow Glass Microspheresmentioning
confidence: 99%